Al-Qur'an as Legitimacy for the Rejection of a Female President in the Context of Presidential Elections In Indonesia - Sidik Pramono, Muhamad (UIN Mataram, 2024)
This article explores the role of the Qur'an in perpetuating the rejection of female presidential candidates in the context of Presidential Elections in Indonesia from 2004 - 2024. To date, Indonesia has not had a female president directly elected by the people. In 2004, Megawati Soekarno Putri became the first woman to run for president. There was both support and rejection of Megawati's candidacy. The rejection response by some groups was based on the teachings of Islam. The rejection of women's leadership as president was based on the Qur'an surah An-Nisa verse 34. After the 2004 and 2009 presidential elections, there were no presidential candidates from among women. The use of the Qur'anic verse to reject a female president is a latent problem even though there are no female presidential candidates in the presidential elections in Indonesia. This means that the use of the Qur'an to reject a female president in Indonesia could still happen in the future. The method used is a literature study with qualitative analysis by utilising primary sources on presidential elections and female presidential candidates. In this article, three discussions will be discussed. First, the use of the Qur'an to reject women's leadership in the presidential election in Indonesia. Second, the rejection of the president with the legitimacy of the Qur'an is a latent problem of the future. Third, how does the alternative narrative of al-Qur'an support women's leadership in the realm of presidential elections?